(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
Analysis of Garlic Potential and Competitiveness in Tabanan Regency, Bali Province. Garlic is a commodity that needed by people. Tabanan Regency is one of the regions that produce garlic. However, garlic production is still low, not even sufficient for the needs of Bali Province itself. The research objective was to analyze the potential and competitiveness of garlic in Tabanan Regency. This study uses secondary data, which is the amount of garlic and horticulture production for five years (2017-2021) in Tabanan Regency and Bali Province. The data sourced from Central Statistics of Tabanan Regency and Bali Province. This study uses two analytical methods, Location Quotient Analysis (LQ) and Shift Share Analysis. The results of this study indicate that garlic in Tabanan Regency is a superior commodity that has potential to be developed, but has low competitiveness compared to reference areas. This is proven by the results of LQ value which is more than one, as well as the results of Shift Share Analysis in Differential Shift section which has a negative value.